The association between pesticide exposure and spontaneous abortion in Brebes, Central Java, Indonesia - Denny, Hanifa Maher
A case control study was conducted among 671 females in Brebes Regency, Central Java, Indonesia in 1999. Brebes is not just the largest onion producer but is also one of the heaviest pesticide users in the country.The general objective of this study was to characterize the nature and the strength association between pesticide exposure and spontaneous abortion. Pesticide exposure was measured in terms of involvement in and duration of agricultural work which can include farming, and other activities which involve direct handling of pesticides. Maternal exposure to pesticides was also measured indirectly by measuring the husbands' exposure to pesticides (i.e., the dose of pesticides applied by the respondents' husband) and the overall pesticide exposure index. The timing of exposure was for a 17-month period (12 months before and/or during first 5 months of index pregnancy).The results of the study reveal that women who were involved in agricultural work during the 17-month period of interest were 1.6 times (95CI: 1.11-2.24, p:0.010) more likely to experience spontaneous abortion compared to women without similar exposure. In addition women who had been involved in agricultural work for a period of 1-16 months have 1.8 times (95CI: 1.19-2.62, p: 0.005) the odds of spontaneous abortion compared to women who never had such exposure. Women whose husbands applied high doses of pesticides 2.6 times more to experience spontaneous abortion (95CI: 1.73-3.92, p: 0.000) compared to women whose husband never used pesticides. There is about 1.7 increased in the odds of spontaneous abortion (95CI: 1.08-2.63; p: 0.019) among women who had low index of the overall pesticide exposure compared to women who were not exposed to pesticides. More over women who had high index of the overall pesticide exposure were likely to have 2.2 times higher in the odds of spontaneous abortion compared to women who were not exposed to pesticides (95CI: 1.42-3.39; p: 0.000).In order to minimize the risk of spontaneous abortion brought about by pesticide exposure, the government should educate farmers on the safe and proper way of using pesticides. They also should be encouraged to practice safer alternative to chemical pesticide control. Etiologic studies to determine the possible impact of pesticide exposure on reproductive outcomes such as spontaneous should always include quantitative measures of the amount of exposure.